2021
DOI: 10.5937/jomb0-25315
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hematologic indices and their correlation to hemoglobin A1c among Bosnian children with type 1 diabetes mellitus and their healthy peers

Abstract: Background: Altered level of many hematological parameters have been directly associated with diabetes in adults, while studies on children with type 1 diabetes mellitus are lacking. The aim of this study was to determine hematological indices in diabetic Bosnian children in comparison to healthy controls as well as to correlate their levels to blood glucose and hemoglobin A1c.  Methods: 100 healthy and 100 children with type 1 diabetes mellituss (age 1-18 years) were included in this study. Complete Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(38 reference statements)
5
2
1
Order By: Relevance
“…In our study, independent T-test showed that the mean and standard deviation of monocyte count, basophil count, monocyte %, basophil %, RBC count, Hct, MCV, MCH, RDW-SD, MPV, PDW, PLC-R, and plateletcrit were statistically significantly different between T2DM patients and healthy control group (P <0.05). This was in concurrent findings reported in Nigeria, India, and Bosnia and Herzegovina [ 11 , 18 , 19 ]. In this study, the mean monocyte count, basophil count, monocyte percent, and basophil percent, MPV, PDW, PLC R, and plateletcrit were statistically significantly high in the diabetes group as compared to healthy controls.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, independent T-test showed that the mean and standard deviation of monocyte count, basophil count, monocyte %, basophil %, RBC count, Hct, MCV, MCH, RDW-SD, MPV, PDW, PLC-R, and plateletcrit were statistically significantly different between T2DM patients and healthy control group (P <0.05). This was in concurrent findings reported in Nigeria, India, and Bosnia and Herzegovina [ 11 , 18 , 19 ]. In this study, the mean monocyte count, basophil count, monocyte percent, and basophil percent, MPV, PDW, PLC R, and plateletcrit were statistically significantly high in the diabetes group as compared to healthy controls.…”
Section: Discussionsupporting
confidence: 89%
“…As summarized in Figure 5 , we found an association of increasing non-class-switched memory B cells with age, while transitional B cells were found to decline with both aging and T1D (48; 49). Finally, CBC parameters showed both age and T1D dependent shifts: MCV and MCH increased with age and T1D, while hemoglobin and hematocrit increased in T1D subjects, findings supported by existing literature (50). Along with providing support for the aforementioned findings, we identified several repeating themes pertinent to immune dysregulation in T1D, namely, altered expression of the Th1-associated chemokine receptor CXCR3 and coinhibitory receptor PD-1 on multiple T cell subsets, as well as increased expression of HLA-DR on monocytes ( Figure 5 ), which we explored further using our novel age-correction approach as described below.…”
Section: Resultssupporting
confidence: 88%
“…Within this study, we replicated multiple findings in smaller cohort studies of T1D subjects compared to CTR (4345; 4750), as well as immune aging studies (3639), providing support for both the age prediction and T1D prediction capacity of the model generated herein. Moreover, we identified novel phenotypes of immune system changes with age and T1D, and have made this dataset readily accessible in an interactive format for public visualization and comparisons to other diseases and cohorts of interest.…”
Section: Discussionsupporting
confidence: 74%
“…There are many studies conducted in different countries showing variations in hematologic indices, some studies showed significance, while others did not. The mean and SD of basophil, monocyte, RBCs, MCH, and MCV were statistically variant between DM and HC groups in Dessie and Gondar cities of Ethiopia, Bosnia and Herzegovina, India, Sudan, and Nigeria 4 , 35 – 37 , 46 , 47 . The findings report of monocyte and basophil in Nigeria were significantly low in DM as compared to HC group 47 while other studies in Turkey, Ethiopia, and India in which monocyte was statistically high in DM group as compared to HC group 36 , 48 , 49 .…”
Section: Discussionmentioning
confidence: 90%